APLIKASI BAHASA JEPANG UNTUK TURIS INDONESIA YANG ADA DI JEPANG - Tungga, Rega Jeatreya; Amin, Fatkhul (Proceeding SENDI_U, 2020)
Japanese is a language that is quite difficult to learn considering that the letters and the coheracy useddiffer from the Indonesian language, therefore the teaching must be done with various innovations deepen LMU.There are three kinds of Japanese letters, hiragana characters, katakana characters, and kanji characters.Especially the Indonesian tourists need to be aware if there are already many Japanese citizens of Japan rules inJapan. The difficulties of Indonesian tourists if they do not speak English at all correctly if they want to do notknow the direction while the language used in the Japanese language. In the application of a solution to proposea solution that is Japanese language applications for tourist Indonesia in Japan. This application is speciallydesigned for Indonesian tourists to work directly with Japanese people. In this application, there are alsoexplanations of each word and sentence and when it is used. To easily memorize the pattern of sentences andletters there is a practice of trying when. The multiple-choice form consists of 10 pieces. In the dual choice ofquestions, there is a function of the Fisher-Yates algorithm that is useful to confuse the problem. Then for the finalresult of getting a 1 to 5-star star using the Fuzzy method Tsukamoto. Fuzzy Tsukamoto Supporters of the decisionto find the final value. The result of each membership function results in 0.5 and 0. There are more and morequestions to be done by many stars.